Colony composition and nutrient analysis of Polyrhachis dives ants, a natural prey of the Chinese pangolin (Manis pentadactyla). Issue 2 (5th October 2021) - Xu, Na; Yu, Jiaming; Zhang, Fuhua; Wu, Shibao; Zou, Cuiyun; Wang, Qiaoyun; Wang, Yifu
Abstract: The Chinese pangolin ( Manis pentadactyla ) is a critically endangered mammal with a highly specialized diet. To enhance nutritional knowledge of its diet, we analyzed the colony composition of a nest of Polyrhachis dives ants, which is the key natural prey in the Chinese pangolin's diet. In addition, we determined the nutrient composition of the total colony compared with adult ants. Nutrients quantified in this study included: crude protein, crude fat, carbohydrate, and amino acids, minerals, and vitamins, as well as formic acid and chitin, which have not been reported in previous diet studies. Our results showed that the colony consisted of adults (82%), pupae (10%), larvae (7%), and eggs (1%) (fresh mass). Both the total colony and adult ants, respectively, contained high concentrations of crude protein (62.97% and 64.68%), chitin (49.25% and 60.40%), crude fat (10.12% and 9.91%) (dry matter basis), and formic acid (2.06% and 3.07%) (fresh mass). This implies that Chinese pangolin might prefer prey with high protein, high chitin, low fat, and low formic acid content. Colony and adult ants differed in chemical composition in many aspects, thus it might be unsuitable to feed Chinese pangolin with only adult ants. Chitin and formic acid may play important roles in the diet and selectivity of Chinese pangolin. This study provides reference information that may be useful for developing better artificial diets with more comprehensive nutrient compositional data to meet the nutritional requirements of the Chinese pangolin under managed feeding programs. Abstract : Polyrhachis dives, which is a common ant species, is a favorite natural prey in Chinese pangolins' diet. The colony member in the ant consist of larvae (a), pupae (b, f: white arrows pointed to), adult ants (c: worker, d: soldier, e: male), and eggs (f: red arrow pointed to). We determined the nutrient composition of the colony and adult ants, respectively, and found the colony and adult ants differed in chemical composition in many aspects. The colony and adult ants, respectively, contained high concentrations of crude protein (62.97% and 64.68%), chitin (49.25% and 60.40%), crude fat (10.12% and 9.91%) (dry matter basis), and formic acid (2.06% and 3.07%) (fresh mass). This study provides reference information, which may be useful for developing better artificial diets to meet the nutritional requirements of Chinese pangolin. Research highlights: 1) Colony and adult ants differed in chemical composition in many aspects, thus it might be unsuitable to feed Chinese pangolin with only adult ants. 2) Chitin and formic acid may play important roles in the diet and selectivity of Chinese pangolin. 3) This study provides reference information that may be useful for developing better artificial diets with more comprehensive nutrient compositional data to meet the nutritional requirements of Chinese pangolin under managed feeding programs.